“The Girl Must Stay Quiet”: Marginalisation of Young Women in Political Spaces and the Impact of Gender Socialization and Ethnic Background - Guglielmi, Simona; Riniolo, Veronica; Maggini, Nicola; Marta Visioli,; Sanarico, Alice (SocietàMutamentoPolitica, 2025)
Studies on youth political participation reveal how engagement levels and forms differ due to gender, socioeconomic resources, and cultural backgrounds. Three key aspects are highlighted: first, political inequalities originate in adolescence, shaped by family political socialization, influencing gender differences, ideology, and ethnic disparities. Second, youth political engagement is affected by intersectional power dynamics, including gender and ethnicity. Third, young people face political institutions that are systematically gendered, with rules that have “gendered effects,” and must navigate male-dominated cultures. This article contributes empirical evidence on the relationship between political socialization, gender norms, and participation among late adolescents and young adults, using an intersectional framework. It employs an Explanatory Sequential Mixed Methods Design. The quantitative phase draws on Eurobarometer Youth survey and the MAYBE project (a multilevel survey with 2,756 Lombardy students, aged 18-20, from 81 schools and 165 classes). The qualitative phase consists of 3 focus groups (participants: 7 men, 14 women, 7 with migrant backgrounds, aged 18-35 in Lombardy), collected by YEP! Youth Equality Participation. The article emphasizes the need to address gender biases in socialization and political practices to foster inclusivity, while highlighting the additional challenges faced by young women from migratory family backgrounds.